The future of Air Force motion imagery exploitation : lessons from the commercial world - Menthe, Lance; Cordova, Amado; Rhodes, Carl A., 1970-; Costello, Rachel; Sullivan, Jeffrey; Project Air Force (U.S.). Force Modernization and Employment Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 2012)
Dramatic changes in the security environment in the past two decades have led to a greatly increased demand for U.S. Air Force intelligence, surveillance, and reconnaissance (ISR) capabilities. Today, the Air Force must provide ISR to support a growing set of missions while remaining postured to support major combat operations (MCOs) should the need arise. To meet these requirements, the Air Force is currently undertaking unprecedented measures to expand and enhance its ISR capabilities. Particular urgency has been attached to cultivating its fleet of sophisticated remotely piloted aircraft (RPA) to support current operations in Afghanistan and Iraq. Equally critical to these efforts, however, is the Air Force$1 (Bs extensive processing, exploitation, and dissemination (PED) force, which is essential to convert the raw data collected into usable intelligence and deliver it to the warfighter. It is therefore imperative to assess the size and mix of the Air Force$1 (Bs PED force to ensure that the ability to conduct all necessary PED within required timelines keeps pace with the increases in the amount and type of information collected. This study addressed the particular challenges associated with the exploitation of motion imagery within the Air Force Distributed Common Ground System (DCGS). Motion imagery collections from full-motion video (FMV) sensors on RPAs have risen rapidly to the point at which they now consume the largest share of Air Force DCGS resources, and new wide-area motion imagery (WAMI) sensors now being deployed have the potential to vastly increase the amount of raw data collected. The information explosion resulting from these vast amounts of motion imagery threatens to leave Air Force intelligence analysts drowning in data. One approach to meeting these challenges was inspired by an examination of related practices in the commercial world. It consists of implementing certain process changes and adopting a new organizational construct to improve the effectiveness of Air Force intelligence analysts while confronting the reality of limited resources.s
Introduction: The Rise of Motion Imagery -- Commercial Practices: Implications for the Air Force -- Way Ahead: Area-Centric Operations -- Conclusion: Lessons from the Commercial World.
"RAND Project Air Force."
Includes bibliographical references (p. 49-51).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force. -- Distributed Common Ground System; Aerial reconnaissance -- United States; Closed-circuit television -- United States; Imaging systems -- United States; Military intelligence -- United States; Military surveillance -- United States; Motion perception (Vision)